Antiemetic Corticosteroid Rotation from Dexamethasone to Methylprednisolone to Prevent Dexamethasone‐Induced Hiccup in Cancer Patients Treated with Chemotherapy: A Randomized, Single‐Blind, Crossover Phase III Trial. (7th July 2017) - Go, Se‐Il; Koo, Dong‐Hoe; Kim, Seung Tae; Song, Haa‐Na; Kim, Rock Bum; Jang, Joung‐Soon; Oh, Sung Yong; Lee, Kyung Hee; Lee, Soon Il; Kim, Seong‐Geun; Park, Lee Chun; Lee, Sang‐Cheol; et al.
Abstract: Background: To assess whether the rotation of dexamethasone to methylprednisolone decreases the intensity of dexamethasone‐induced hiccup (DIH) in cancer patients treated with chemotherapy. Materials and Methods: Adult patients who experienced DIH within 3 days after the administration of dexamethasone as an antiemetic were screened. Eligible patients were randomly assigned to receive dexamethasone ( n  = 33) or methylprednisolone ( n  = 32) as an antiemetic (randomization phase). In the next cycle of chemotherapy, the dexamethasone group received methylprednisolone and vice versa in the methylprednisolone group (crossover phase). The primary endpoint was the difference in hiccup intensity as measured using the numeric rating scale (NRS) between two groups. Results: No female patients were enrolled, although the study did not exclude them. At the randomization phase, hiccup frequency was 28/33 (84.8%) in the dexamethasone group versus 20/32 (62.5%) in the methylprednisolone group ( p  = .04). Intensity of hiccup was significantly higher in the dexamethasone group than that in the methylprednisolone group (mean NRS, 3.5 vs. 1.4, p  < .001). At the crossover phase, hiccup intensity was further decreased after the rotation of dexamethasone to methylprednisolone in the dexamethasone group (mean NRS, 3.5 to 0.9, p  < .001), while it was increased by rotating methylprednisolone to dexamethasone in the methylprednisolone group (mean NRS, 1.4 to 3.3, p  = .025). There were no differences in emesis intensity between the two groups at either the randomization or crossover phases. Clinicaltrials.gov identifier: NCT01974024. Conclusion: Dexamethasone‐induced hiccup is a male‐predominant phenomenon that can be ameliorated by rotating dexamethasone to methylprednisolone without compromising the antiemetic efficacy. Abstract : Dexamethasone is an established agent for the prevention of chemotherapy‐induced nausea/vomiting; however, even a short course of dexamethasone can cause many adverse effects, such as insomnia, indigestion, weight gain, acne, and hiccupping. Although often regarded trivial, persistent hiccups can cause depression, insomnia, and malnutrition. The objective of this study was to determine whether the rotation of corticosteroids affects the incidence and intensity of dexamethasone‐induced hiccup without compromising the antiemetic efficacy.